Alpha Amylase as a Salivary Biomarker of Acute Stress of Venepuncture from Periodic Medical Examinations - Koh, David; Ng, Vivian; Naing, Lin (Frontiers in Public Health, 2014)
Periodic occupational health examinations often require venepuncture. Acute psychological and physical stressors during such a procedure result in sympathetic stimulation and increased salivary protein secretion, including salivary alpha-amylase (SAA). We studied SAA response to venepuncture during such an examination. Fifty eight healthy males undergoing periodic medical examination reported perceived stress level (PSL) scores (on a 5-point scale) and provided passive drool saliva samples at 15-min (T1) and 1-min before (T2); and 1-min (T3) and 15-min after venepuncture (T4). A subset of 33 participants available for repeat examination on a control day when there was no venepuncture provided saliva samples at the corresponding times for comparison. Saliva SAA activity levels were analysed using a salivary α-amylase assay kit (Salimetrics LLC, USA) Among 58 participants, mean SAA increased from T1 (89.95 U/L) to T2 (109.5 U/L) and T3 (116.9 U/L). SAA remained elevated 15 minutes after venepuncture (121.0 U/L). A positive trend in the difference of SAA between T3 and T1 was noted among subjects with increasing mean PSL scores. T3-T1 values were 0.6 (among those with PSL ≤ 1, n=24), 11.3 (among those with PSL between 1 and 1.5, n= 18) and 78.9 (among those with PSL >1.5, n=16). SAA increment over 4 time points was significantly higher on the venepuncture compared to the control day (p=0.021). SAA increases in response to the acute stress of venepuncture during a periodic medical examination, and remains elevated 15 minutes after the procedure. In comparison, such fluctuations in SAA were not seen on a control day. During venepuncture, increase in SAA from baseline is higher among those who reported greater self-perceived stress during the procedure.